P349 Relationship between genotypes and in vitro pathogenic behavior of Uruguayan strains of Cryptococcus spp. (20th September 2022) - Cabeza, Elisa; Arteta, Zaida; Betancor, Laura
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM:   Objective: Contribute to the knowledge of the relationship between genetic and pathogenic characteristics of meningeal cryptococcosis-producing strains from Uruguay. Methods: We have included a total of 21 isolates of Cryptococcus spp from human cases of meningoencephalitis. We start from the general strain collection of the mycology laboratory of the department of parasitology and mycology, medical school, University of the Republic. The strain was sectioned taking into account the phenotypic diversity and genetic diversity through a previous analysis by PCR fingerprinting, for study by MLST. MLST was performed according to the protocol available at: http://mlst.mycologylab.org/defaultinfo.aspx?Page=CryptoHome . Infection, intracellular survival, and cell proliferation assays were performed. The murine macrophage cell line J774 (ATCC TIB 67) was used. Results: Of the 21 strains studied, in 13 we obtained an ST that had been previously reported (9 C. neoformans complex and 4 C. gattii complex). For the remaining 8 strains, we obtained new allelic combinations to which new STs were assigned, which were deposited in the MLST database for Cryptococcus spp. (http://mlst.mycologylab.org) (Table 1). All strains were phagocytosed and all were able to persist within macrophages at 24 h post-infection, although there was great variability between strains (Table 1). In most of the strains, the control of macrophages prevailed through cell lysis mechanisms over Cryptococcus spp, with one proliferation index (PI) ˂1.0. In the proliferation assay, only 4 strains managed to proliferate within the macrophages, 3 of them correspond to C. gattii complex, genotypes VGI and VGII. The 4th strain that achieved proliferation was corresponding to the VNI genotype. Conclusion: We obtained a clear differentiation of in vitro behavior between the strains corresponding to C. neoformans complex and C. gattii complex. The strains belonging to C. gattii complex presented less phagocytosis and greater persistence and intracellular proliferation.